Investor Information Demand: Evidence from Google Searches Around Earnings Announcements - DRAKE, MICHAEL S.; ROULSTONE, DARREN T.; THORNOCK, JACOB R. (Journal of Accounting Research, 2012)
ABSTRACT The objective of this study is to investigate factors that influence investor information demand around earnings announcements and to provide insights into how variation in information demand impacts the capital market response to earnings. The Internet is one channel through which public information is disseminated to investors and we propose that one way that investors express their demand for public information is via Google searches. We find that abnormal Google search increases about two weeks prior to the earnings announcement, spikes markedly at the announcement, and continues at high levels for a period after the announcement. This finding suggests that information diffusion is not instantaneous with the release of the earnings information, but rather is spread over a period surrounding the announcement. We also find that information demand is positively associated with media attention and news, and is negatively associated with investor distraction. When investors search for more information in the days just prior to the announcement, preannouncement price and volume changes reflect more of the upcoming earnings news and there is less of a price and volume response when the news is announced. This result suggests that, when investors demand more information about a firm, the information content of the earnings announcement is partially preempted.